Questions & Answers

Question

Answers

Answer

Verified

158.7k+ views

Hint: Start by analysing the pattern of numbers given and then generalise the equation, after that put the values in the generalized equation by putting the values asked in question.

Complete step-by-step answer:

If you carefully observe the numbers, you can see that the rule is

$a \times b = \left( {a + b} \right)\left( {ab} \right)$

Therefore,

$5 \times 1 = \left( {5 + 1} \right)\left( {5 \times 1} \right)$

$5 \times 1 = 65$

Answer = $65$

Note: In these types of questions start by generalising the series and then solving the term asked in the question by assigning the values in the equation.

Complete step-by-step answer:

If you carefully observe the numbers, you can see that the rule is

$a \times b = \left( {a + b} \right)\left( {ab} \right)$

Therefore,

$5 \times 1 = \left( {5 + 1} \right)\left( {5 \times 1} \right)$

$5 \times 1 = 65$

Answer = $65$

Note: In these types of questions start by generalising the series and then solving the term asked in the question by assigning the values in the equation.